The problem-based learning model with statistics board in improving students' problem-solving abilities - Hersanasti, Wulan; Choirudin, Choirudin; Setiawan, Agus; Zoker, Exton Mohamed; Santiago, Paulo Vitor da Silva (Institut Studi Islam Muhammadiyah (ISIMU) Pacitan, 2024)
This research aims to determine the differences in problem-solving abilities between students who receive teaching through a problem-based learning approach supported by teaching aids and students who receive direct teaching in statistics subjects in class VIII. This research method is quantitative, and it applies a repeated experimental research type with a research design (pre-test-post-test control group design). This research was conducted at MTs Ma'arif Roudhotut Tholibin with samples of classes VIII A and VIII B. Data collection instruments were assessment validation sheets, pre-test and post-test sheets and documentation. The data analysis technique used is the Independent samples t-test. This research shows that the average score for students who used the problem-based learning model with statistics board teaching aids was 81.30, and the student's group who used the direct learning model was 59.80. Thus, descriptively, it can be concluded that there is a significant difference between the problem-solving abilities of the students group who use the problem-based learning model with statistics board teaching aids and the students group who use the direct learning model.